2008
DOI: 10.1002/ajim.20555
|View full text |Cite
|
Sign up to set email alerts
|

Causes of work‐related injuries among young workers in British Columbia

Abstract: Safety training should be provided before YWs start work and in media other than school. Seatbelt use should be addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 2 publications
4
12
0
Order By: Relevance
“…It has been reported that occupational accidents are more common in males (84-86%) [10-13], and our results correlate with the literature. More participation of males in work life possibly contributes to this finding.…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that occupational accidents are more common in males (84-86%) [10-13], and our results correlate with the literature. More participation of males in work life possibly contributes to this finding.…”
Section: Discussionsupporting
confidence: 92%
“…However, the data does clearly indicate that workers in small businesses were at twofold risk of a fatal injury within the first week of employment, and fourfold risk of fatal injury within the first month of employment compared with new workers employed by larger businesses. This is consistent with our previous report of the time pattern of serious injuries among young workers (Holizki et al, 2008).…”
Section: Discussionsupporting
confidence: 93%
“…Despite these benefits, there are drawbacks associated with youth employment, including increased high-school dropout rates with decreased overall educational attainment [National Research Council, 1998]. Furthermore, younger workers, including both adolescents (age 15-19 years) and young adults (age 20-24 years) are at higher risk for experiencing workplace injuries [Runyan and Zakocs, 2000; National Institute for Occupational Safety and Health, 2004;Salminen, 2004;Breslin and Smith, 2005;McCall et al, 2007;Holizki et al, 2008]. Younger workers may be vulnerable because of a number of factors, including lack of experience; dearth of training coincident with lack of supervision; and a lack of physical or cognitive maturity [Massachusetts Department of Public Health, 1998;Runyan and Zakocs, 2000; National Institute for Occupational Safety and Health, 2003;Baron, 2005].…”
Section: Introductionmentioning
confidence: 98%